Variability analysis and empirical estimation of solar radiation at Ludhiana - Kingra, P.K. (Annals of Agricultural Research, 2018)
Solar radiation is one of the most important input components for agriculture. Both quality andquantity of solar radiation has a significant effect on crop productivity in any region. The two mainplant physiological processes i.e. photosynthesis and transpiration are directly affected by solarradiation. Solar radiation in the wavelength range of 0.4 - 0.7 Î¼ is absorbed by the plants for theprocess of photosynthesis. Thus, the availability of accurate quantitative data of solar radiation is ofparamount importance for conducting scientific studies on plant physiological processes andagricultural productivity. Such studies are difficult to conduct if accurate solar radiation data is notavailable. In the absence of trustworthy solar radiation data, empirical models for estimation ofsolar radiation from other climatological parameters especially sunshine hours, are indispensable.In the present investigation, solar radiation for Ludhiana was first computed from different weatherparameters using CROPWAT model and then linear regression models were developed to estimatedaily average solar radiation directly from sunshine hours data on monthly and annual basis. Trendanalysis of mean annual solar radiation and sunshine hours indicated a decreasing trend (R2 = 0.39and 0.41, respectively). Linear regression models were observed to estimate solar radiation in verygood agreement with the solar radiation computed from CROPWAT model with R2 > 0.98 for all themonths, which indicates that these models can be used very successfully for empirical estimation ofsolar radiation from sunshine hours during any period of the year under central Punjab conditions.